The Oral Thrombin Inhibitor Dabigatran: Strengths and Weaknesses - Schulman, Sam; Majeed, Ammar (Seminars in Thrombosis and Hemostasis, 2012)
Since the quest for a better replacement of warfarin started several decades ago and new compounds were brought forward to clinical trials, the concept of an ideal anticoagulant frequently became presented in lectures and articles. We have here reviewed strengths and weaknesses of the oral thrombin inhibitor dabigatran in terms of pharmacokinetics and clinical data. When strengths clearly exceed the weaknesses for any characteristic, the drug fits into the concept of an ideal anticoagulant in that domain. It is evident that dabigatran does not accomplish that concept for all characteristics but it reaches well above warfarin. We believe it is unlikely that any drug will fulfill all criteria for the ideal anticoagulant. Laboratory testing for dabigatran will not be discussed in any detail in this article, which is instead the focus of other articles from this issue of Seminars in Thrombosis & Hemostasis.
Keywords: dabigatran; warfarin; low-molecular-weight heparin; efficacy; bleeding